2014
DOI: 10.15171/jcvtr.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peripheral edema on cuff-based/oscillometric blood pressure measurements accuracy

Abstract: Introduction: Blood pressure (BP) measurement is essential for epidemiological studies and clinical decisions. It seems that tissue characteristics can affect BP results and we try to find edema effect on BP results taken by different methods. Methods: BP of 55 children before open heart surgery were measured and compared according to three methods: Arterial as standard and reference, oscillometric and auscultatory methods. Peripheral edema as a tissue characteristic was defined in higher than +2 as marked ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…In a study on children (age, 29.4 ± 3.9 months, n = 55), MPMs and auscultatory methods were shown to underestimate SBP and DBP compared to IABP methods in presence of limb edema. 13 Lower NIBP values in edematous limbs in our study supports this observation, and suggest clinicians to be cautious as edema is common among sepsis patients in LMICs. 25 27 Though MPM measurements were not affected by inotropes in adults, 11 they seem to overestimate readings among children with high VIS >40.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a study on children (age, 29.4 ± 3.9 months, n = 55), MPMs and auscultatory methods were shown to underestimate SBP and DBP compared to IABP methods in presence of limb edema. 13 Lower NIBP values in edematous limbs in our study supports this observation, and suggest clinicians to be cautious as edema is common among sepsis patients in LMICs. 25 27 Though MPM measurements were not affected by inotropes in adults, 11 they seem to overestimate readings among children with high VIS >40.…”
Section: Discussionsupporting
confidence: 85%
“… 15 Intra-arterial blood pressure readings are reportedly similar to auscultatory NIBP readings among critically ill children (age, 29.4 + 3.9 months). 13 In our study, overestimation of SBP, DBP, and MAP by MPMs, irrespective of age, gender, and critical care characteristics are in agreement. In contrast, Wong et al, reported underestimation (by about 4–5 mm Hg) by two AODs (Welch-Allyn® Vital Sign monitor and Dinamap Procare-120®) compared to MCS in outpatient setting (age, 5–15 years).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The increased body weight during pregnancy, neonatal birthweight, gestational age, maximum SBP and diastolic BP (DBP), level of albumin and urine protein in 24 h, duration of hypertension, the severity of HDP, and the level of edema were also recorded. Edema was classified in standard grade by a physician as follows:[ 21 ] (1 = A normal foot and leg contour with a barely perceptible pit; 2 = Fairly normal lower extremity contours with a moderately deep pit; 3 = Obvious foot and leg swelling with a deep pit; 4 = Severe foot and leg swelling that distorts the normal contours with a deep pit).…”
Section: Ethodsmentioning
confidence: 99%